“First-time mother knew nothing”: the experiences of primiparous women in childbirth and puerperium (Research, Society and Development, 2020)
Objective: to understand the experience of primiparous women in childbirth and puerperium. Method: qualitative study, developed with primiparous puerperanwomen. The data were produced through semi-structured interviews and submitted to thematic analysis. Results: the findings of the interviews were divided into two thematic categories. The first one covers the experiences related to the giving birth process and was entitled “Nothing happened that I imagined”: the experience of primiparous women in childbirth. The second called “It seemed to be easier, but not”: the experience of primiparous women in the puerperium addresses the experiences of primiparous women in the puerperium. Conclusions: it is observed that the incompleteness of professional guidelines marked the experiences of primiparous women in childbirth and puerperium, leading to fear, insecurity and doubts about these events. From this perspective, it is understood that health education is a primordial element of care for women during the pregnancy-puerperal period, capable of collaborating for a positive experience of this whole process.